2015
DOI: 10.1001/jamaoncol.2015.2151
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymerase e–Mutated and Microsatellite-Instable Endometrial Cancers With Neoantigen Load, Number of Tumor-Infiltrating Lymphocytes, and Expression of PD-1 and PD-L1

Abstract: he Cancer Genome Atlas project identified 2 groups of endometrioid endometrial cancers (ECs) with high mutation frequency: an ultramutated group (7% of all tumors) that harbored mutations in the exonuclease domain of polymerase e (POLE), and a hypermutated group (28% of tumors) with microsatellite instability (MSI), the majority of which harbored MLH1 promoter methylation. 1 The ultramutated POLE group exhibited an extremely high mutation rate (232 × 10 −6 mutations/Mb) with a unique nucleotide change spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
491
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(524 citation statements)
references
References 15 publications
28
491
1
4
Order By: Relevance
“…The results of the present study, combined with positive reports from ongoing clinical trials (4,41), suggest that inhibitors of these molecules may be considered as treatments for patients with endometrial tumors. Furthermore, the present study demonstrated that PD-L2 may be a useful target for immune suppression in a small number of patients with endometrial carcinoma, whereas both PD-L1 and B7-H4 were highly expressed in two of the analyzed tumor types, and therefore may be ideal candidate drug targets.…”
Section: B Amentioning
confidence: 53%
“…The results of the present study, combined with positive reports from ongoing clinical trials (4,41), suggest that inhibitors of these molecules may be considered as treatments for patients with endometrial tumors. Furthermore, the present study demonstrated that PD-L2 may be a useful target for immune suppression in a small number of patients with endometrial carcinoma, whereas both PD-L1 and B7-H4 were highly expressed in two of the analyzed tumor types, and therefore may be ideal candidate drug targets.…”
Section: B Amentioning
confidence: 53%
“…The increased tumor‐infiltrating lymphocytes observed in MSI‐high CRC are themselves a sign of immune activation, and it has been hypothesized that the increased mutational burden seen in these tumors could predict immunogenicity and response to immune checkpoint blockade. It is estimated that POLE mutated tumors on average have 15‐fold more neoantigens than MSI tumors and 100‐fold more than typical MSS tumors [17], [18]. …”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…Somatic POLE exonuclease domain mutations (hereafter simply referred to as POLE mutations) occur in sporadic tumours of the endometrium (7–15% cases) 8, 9, colorectum (1–2%) 10, 11, and, less commonly, in other cancers (although, for reasons that are unclear, somatic POLD1 exonuclease domain mutations are very uncommon). POLE ‐mutant colorectal and endometrial cancers have an excellent prognosis 8, 11, 12, 13, probably owing to a robust antitumour immune response against the multitude of immunogenic neoantigens that they are predicted to harbour 11, 14, 15. Very recent reports have also suggested that these tumours may be highly responsive to immune checkpoint inhibition 16.…”
Section: Introductionmentioning
confidence: 99%